The rationale, design of the Assisted reproductive technology cohort nested in a pre-pregnancy family cohort (APP-Cohort) - Wei Xiong; Qinghan Liang; Xiaojie Han; Qiaolu Cheng; Qihang Liu; Xifang Zuo; Huiyu Wang; Huijing He; Guangliang Shan (Annals of Medicine)
Introduction Infertility has become a major global issue due to the trend of delaying marriage and advanced maternal age. Family/Birth cohort studies are essential for exploring ways to enhance health outcomes at both the individual and societal levels. However, there is a shortage of cohorts that include families who have utilized assisted reproductive technology (ART), particularly initiated at the early stages before pregnancy. The Assisted Reproductive Technology Cohort (APP-Cohort) is a prospective study aiming to investigate the epidemiology and risk factors of adverse gestational outcomes and other health issues in couples who have conceived through ART or naturally.Methods The cohort study’s baseline survey commenced in January 2022 at several locations in Beijing, and enrollment is currently in progress. Both spouses filled out a questionnaire covering demographic, socio-economic, and various modifiable risk factors to gather information on their lifestyle. Physical examinations and biochemical tests were carried out, alongside regular yearly health check-ups throughout pregnancy and childhood. The survey data will be connected to electronic medical records to compile health information on the couples, newborns, and children.Discussion The APP-Cohort study collected data from both wives and husbands before conception, allowing for early assessment of environmental risk factors for maternal and offspring health. With a focus on various types of risk factors such as genetic, environmental, and shared familial traits, the ongoing follow-up of this study will enable researchers to evaluate and distinguish the impacts of these factors on pregnancy outcomes, perinatal health, and children’s health for individuals conceived naturally versus those conceived through ART. By utilizing practical experience and advanced mathematical analysis of the extensive data, the APP-Cohort study will provide valuable insights to promote the administration and success rate of ART in China.